Developing an architecture for the production of a generic model of the local manufacturing industries - Chiew, Ling King (Faculty of Computer Science and Information Technology, 2006)
The primary purpose of this study is to devise the architecture of a system that can develop a generic model of the restricted local small to medium sized manufacturing industries. With this architecture, a modeling tool or demonstrator system can be developed to capture the process flow of manufacturing industries.